Photo‐enhanced toxicity of fluoranthene to Gulf of Mexico marine organisms at different larval ages and ultraviolet light intensities. (25th February 2016) - Finch, Bryson E.; Stubblefield, William A.
Abstract: Significant increases in toxicity have been observed as a result of polycyclic aromatic hydrocarbon (PAH) absorption of ultraviolet (UV) radiation in aquatic organisms. Early life stage aquatic organisms are predicted to be more susceptible to PAH photo‐enhanced toxicity as a result of their translucence and tendency to inhabit shallow littoral or surface waters. The objective of the present study was to evaluate the sensitivity of varying ages of larval mysid shrimp ( Americamysis bahia ), inland silverside ( Menidia beryllina ), sheepshead minnow ( Cyprinodon variegatus ), and Gulf killifish ( Fundulus grandis ) to photo‐enhanced toxicity and to examine the correlation between photo‐enhanced toxicity and organism pigmentation. Organisms were exposed to fluoranthene and artificial UV light at different larval ages and results were compared using median lethal concentrations (LC50s) and the lethal time‐to‐death (LT50s). In addition, a high UV light intensity, short‐duration (4‐h) experiment was conducted at approximately 24 W/m 2 of ultraviolet radiation A (UV‐A) and compared with a low‐intensity, long‐duration (12‐h) experiment at approximately 8 W/m 2 of UV‐A. The results indicated decreased toxicity with increasing age for all larval organisms. The amount of organism pigmentation was correlated with observed LC50 and LT50 values. High‐intensity short‐duration exposure resulted in greater toxicity than low‐intensity long‐duration UV treatments for mysid shrimp, inland silverside, and sheepshead minnow. Data from these experiments suggest that toxicity is dependent on age, pigmentation, UV light intensity, and fluoranthene concentration. Environ Toxicol Chem 2016;35:1113–1122. © 2015 SETAC